Environmental Law Dictionary: from Theory to Practice - Krieger, Maria; Becker Maciel, Anna; Bevilacqua, Cleci; Lorenci, Maria; Favero, Teresinha; De Oliveira, Marília (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThis paper describes some of the problems encountered in compiling a dictionary of Brazilian environmental law terms and proposed solutions. The major difficulties stemmed from the overlapping of two distinct areas (environmental science and law), each with its own specific requirements. To overcome these hurdles, decisions had to be made which affected the very structure of the dictionary itself.